DIVERSITY AND ABUNDANCE TRENDS OF BENTHIC FORAMINIFERA FROM THE SOUTHERN PART OF THE IRAKLION BASIN, CENTRAL CRETE - Drinia, H.; Antonarakou, A.; Tsaparas, N. (Bulletin of the Geological Society of Greece, 2018)
Benthic foraminiferai fossil assemblages of the Roufas Section, southern Iraklion Basin, central Crete, were analyzed for the first time. Taxonomic and quantitative analyses were made in order to obtain paleoenvironmental (physical as well biological) information. A data set has been subjected to R- and Q-mode cluster analyses in order to demonstrate the linkage between taxa distribution and paleoenvironmental gradients. Our results suggest that oxygenation and trophic conditions of the near-surface sediments are the most important factors that control the community structure of the benthic foraminiferai fauna. The application of the oxygen transfer function - based on the use of benthic foraminiferai taxa from oxyphilic habitats - to the benthic faunas of the Roufas Section, allows the reconstruction of the oxygen contents of the bottom waters. Apart from the middle part of the section, no severe disturbances are recorded, pointing to the fact that we are dealing with an overall rather well ventilated water column during most of the part of the sequence.